Psicología social crítica e intervención psicosocial. Reflexiones y experiencias de investigación - Moncayo Quevedo, Jorge Eduardo (Editorial Bonaventuriana, Universidad de San Buenaventura Cali., 2015)
The topics addressed in this book arise from the reflections that emerged from the IV Meeting of the Network of Social and Critical Psychology held at the University of Manizales (2007), whose debates revolved around the question of what to understand by social and critical psychology, a question that was continued at the fourth meeting held at the Pontificia Universidad Javeriana in Bogotá in 2010, and was complemented with the proposal to think about what is understood by psychosocial. These two questions guide the purpose of the book, which is none other than to try to answer them.